Q: What is 2x2 equals 6x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0

2x2-3 = -6x-2 2x2+6x-3+2 = 0 2x2+6x-1 = 0 When factored with the help of the quadratic equation formula: (2x-0.3166247904)(x+3.1583123952) = 0 Therefore: x = 0.1583123952 and also x = -3.1583123952

2x2 + 6x - 1 = 0 (-6 +/- sqrt (36 - 8)) /4 ( -6 +/- 5.29) / 4 -1.5 +/- 1.32 -2.82 or -0.18

2x2 - 6x - 25 = 0. Solutions are 5.34 and -2.34

2x2-6x+2y+18 = 0. Subtract the 2y from both sides. 2x2-6x+18 = -2y. Divide all by -2 to get y by itself. -x2+3x-9 = y. This graph is going to be a parabola that opens downward, like a frown.

Related questions

2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0

2x2-3 = -6x-2 2x2+6x-3+2 = 0 2x2+6x-1 = 0 When factored with the help of the quadratic equation formula: (2x-0.3166247904)(x+3.1583123952) = 0 Therefore: x = 0.1583123952 and also x = -3.1583123952

2x2 + 6x - 1 = 0 (-6 +/- sqrt (36 - 8)) /4 ( -6 +/- 5.29) / 4 -1.5 +/- 1.32 -2.82 or -0.18

2x2 - 6x - 25 = 0. Solutions are 5.34 and -2.34

Trinomial

2x2-6x+2y+18 = 0. Subtract the 2y from both sides. 2x2-6x+18 = -2y. Divide all by -2 to get y by itself. -x2+3x-9 = y. This graph is going to be a parabola that opens downward, like a frown.

2x2 + 6x - 8 = 72 ∴ 2x2 + 6x + 64 =0 ∴ x2 + 3x + 32 = 0 This can not be factored, as x is not equal to any integer. Using the quadratic equation, we find that: x = -3/2 ± √119 / 2i

x2 plus 6x-2 equal -2x2 plus x ..=7x equal -3x2 ..4x=2x=2 answer ..check it if u dont want to trust ..Improved Answer:x2+6x-2 = -2x2+xx2+2x2+6x-x-2 = 03x2+5x-2 = 0(3x-1)(x+2) = 0x = 1/3 or x = -2The answer can be checked by using the quadratic equation formula.

6x3 - x2 + 17 = 2x2 + 47 6x3 - x2 - 2x2 = 47 - 17 x2(6x - 1 - 2) = 30 this is the simplest factorisation.

your equation is this... 2x3 + 11x = 6x 2x3 + 5x = 0 x(2x2 + 5) = 0 x = 0 and (5/2)i and -(5/2)i

-4x2 + 6x + 40 = 0 ∴ -2x2 + 3x + 20 = 0 ∴ -2x2 - 8x + 5x + 20 = 0 ∴ -2x(x + 4) + 5(x + 4) = 0 ∴ (5 - 2x)(x + 4) = 0 ∴ x ∈ {5/2, -4}

A quadratic polynomial.